Model Pemberdayaan UMKM Berbasis Digitalisasi Potensi Lokal dalam Konteks Pembangunan Desa Berkelanjutan Indonesia - Miya Nurohmah; Asrida Asrida (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
This study analyzes Micro, Small, and Medium Enterprises (MSMEs) model based on local potential to support sustainable rural development through Systematic Literature Review (SLR) using PRISMA method. MSMEs contribute to national economic resilience by creating jobs, increasing income, and strengthening the rural economic structure. However, their development is hindered by limited digital literacy, unequal access to technology, and restricted financial resources. The reviewed literature identifies four essential pillars of an effective empowerment model: (1) value chain development grounded in local resources, (2) penta-helix collaboration among government, academia, industry, communities, and media, (3) institutional strengthening at the village level, and (4) the acceleration of innovation and digital transformation, including the use of artificial intelligence to enhance marketing performance and efficiency. Integrating local potential with digital technology broadens market reach, improves production processes, and enhances progress toward Sustainable Development Goals (SDGs). Successful implementation requires comprehensive policy support, improved digital infrastructure, and enhanced technological skills among MSME actors. This study proposes a conceptual framework to guide stakeholders in designing adaptive empowerment strategies that align with the ongoing digital transition. Further empirical research is recommended to validate the model and explore the broader role of artificial intelligence in reinforcing MSME sustainability in rural contexts.